2007
DOI: 10.1002/app.27143
|View full text |Cite
|
Sign up to set email alerts
|

Tensile behavior of glass‐fiber‐filled polyacetal: Influence of the functional groups of polymer matrices

Abstract: We investigated the tensile behavior of glass-fiber-filled polyacetal [i.e., polyoxymethylene (POM)], focusing on the mutual influence of the functional groups in the POM matrices and the glass binder system. The different POM matrices were compounded with three kinds of glass fibers (20 wt %) treated with different glass binders, namely, epoxy resin, thermoplastic polyurethane (TPU), and a mixture of TPU and epoxy resin. A good correlation between the tensile strength and elongation at break was observed, reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Nevertheless, up to now, lots of efforts have been devoted to further improvement of the mechanical strength of POM by means of incorporation with fillers such as calcium carbonate, talc, diatomite, clay, and glass fibres. Several authors reported that due to addition of glass fibre the heat deflection temperature of POM was found to increase about 20-40 ∘ C [6][7][8]. Addition of glass fibre with POM increases the mechanical and thermal properties with 25% ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, up to now, lots of efforts have been devoted to further improvement of the mechanical strength of POM by means of incorporation with fillers such as calcium carbonate, talc, diatomite, clay, and glass fibres. Several authors reported that due to addition of glass fibre the heat deflection temperature of POM was found to increase about 20-40 ∘ C [6][7][8]. Addition of glass fibre with POM increases the mechanical and thermal properties with 25% ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The polyacetal copolymers show high heat stability and a longterm mechanical and physical properties, although they have lower crystallinity and lower short-term mechanical strength in comparison with polyacetal homopolymers [3,4]. For these beneficial properties, they have been applied to replace metals and ceramics in microelectronic packaging, aerospace, automotive, and biomedical applications [1,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…If the fiber diameter is larger, there is a higher probability of material defects and damages describe in literature as micronotches and microcracks [18].Many groups of researchers conduct research on polymer composites with glass fiber. It has been revealed that glass fibers successfully strengthen polymers causing better strength properties, higher resistance to creep, and fatigue, as well as provide greater dimensional stability [19][20][21][22].POM is a thermoplastic material with a high degree of crystallinity. This polymer is obtained from formaldehyde by homopolymerisation (POM-H) or copolymerization with cyclic ethers (POM-C).…”
mentioning
confidence: 99%